2021
DOI: 10.3389/fimmu.2021.628156
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Arginase 1 Insufficiency Exacerbates Amyloid-β Associated Neurodegenerative Pathways and Glial Signatures in a Mouse Model of Alzheimer’s Disease: A Targeted Transcriptome Analysis

Abstract: Brain myeloid cells, include infiltrating macrophages and resident microglia, play an essential role in responding to and inducing neurodegenerative diseases, such as Alzheimer’s disease (AD). Genome-wide association studies (GWAS) implicate many AD casual and risk genes enriched in brain myeloid cells. Coordinated arginine metabolism through arginase 1 (Arg1) is critical for brain myeloid cells to perform biological functions, whereas dysregulated arginine metabolism disrupts them. Altered arginine metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…The key enzyme in this pathway, arginase (ARG2) was positively associated with AD in our data. It catalyzes the conversion of arginine to ornithine with urea as a byproduct and has been previously linked to AD pathology due to its involvement in microglial activation and autophagy (6668). Moreover, the reduction of urea levels through the inhibition of arginase (ARG2) has been suggested as a promising target in the context of AD (69).…”
Section: Resultsmentioning
confidence: 99%
“…The key enzyme in this pathway, arginase (ARG2) was positively associated with AD in our data. It catalyzes the conversion of arginine to ornithine with urea as a byproduct and has been previously linked to AD pathology due to its involvement in microglial activation and autophagy (6668). Moreover, the reduction of urea levels through the inhibition of arginase (ARG2) has been suggested as a promising target in the context of AD (69).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, too much APP may also impair remyelination, as the same study also found decreased OLs in analogous human AD post-mortem tissues. A possible mechanism of myelin repair may be tied to Arginase 1 (Arg1) expression , as bulk RNA transcriptome analysis and cell type-profiling of APP mice demonstrated a significant association between insufficient Arg1 expression in myeloid cells, including OLs and other glial and phagocytic cells, and subsequent neurodegeneration and Aβ deposition [ 24 ]. Counterintuitively, Arg1 deficiency promotes OLs; more expectedly, it upregulates pro-inflammatory markers.…”
Section: Examining Overlaps Between Myelin Repair and Ad Signaling Pa...mentioning
confidence: 99%
“…LPL deficiency has been thoroughly investigated as a possible contributing factor in the development of AD [25,[70][71][72]. LPL administration results in elevated cellular Arg1 levels [25], which has been previously implicated in myelin repair [24]. Lipid uptake may also be mediated by colony-stimulating factor 1 receptor, which, when inhibited, reduces microglia but potentially enhances the phagocytic capacity of remaining microglia, thus enabling remyelination [73].…”
Section: Apoe and Lipid Metabolismmentioning
confidence: 99%
“…The key enzyme in this pathway, arginase (ARG2) was positively associated with AD in our data. It catalyzes the conversion of arginine to ornithine with urea as a byproduct and has been previously linked to AD pathology due to its involvement in microglial activation and autophagy 64–66 . Moreover, the reduction of urea levels through the inhibition of ARG2 has been suggested as a promising target in the context of AD 67 …”
Section: Resultsmentioning
confidence: 99%